Solid Waste Disposal and its Management: a Case of Sibsagar Urban Area in Assam, India - Dutta, Bristi (International Journal of Bio-resource and Stress Management, 2023)
Widespread industrial development and unplanned urbanization has resulted in the creation of ever increasing problem of solid waste disposal and its management, which has been experienced mostly in the developing countries including India. Moreover, advanced waste management techniques are not used in India. It is high time to think about a technique which can be practised easily to reduce the impact of waste problem permanently without affecting the environment and biodiversity. In the present study, a few waste-prone areas were selected in Sivasagar town area of Assam state in India. Heaps of garbage is a familiar sight in these places. Though Sivasagar municipality board has arrangement to collect and dispose the garbage at a fixed place, the way they dispose seems unscientific and unhygienic. Also the guidelines are not followed properly. The study aims to find the reason behind such incidence and to recommend a solution which is environmentally sound and easily applicable.